2005
DOI: 10.1002/for.966
|View full text |Cite
|
Sign up to set email alerts
|

Statistical surveillance of cyclical processes with application to turns in business cycles

Abstract: On-line monitoring of cyclical processes is studied. An important application is early prediction of the next turn in business cycles by an alarm for a turn in a leading index. Three likelihood based methods for detection of a turn are compared in detail. One of the methods is based on a Hidden Markov Model. The two others are based on the theory of statistical surveillance. One of these is free from parametric assumptions of the curve. Evaluations are made of the effect of different specifications of the curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Albers and Kallenberg (2004) conclude that for the Shewhart method the sample size of the estimate has to be very large. Andersson et al (2005) make the same conclusion for other methods.…”
Section: Change Between Unknown Parameterssupporting
confidence: 63%
See 1 more Smart Citation
“…Albers and Kallenberg (2004) conclude that for the Shewhart method the sample size of the estimate has to be very large. Andersson et al (2005) make the same conclusion for other methods.…”
Section: Change Between Unknown Parameterssupporting
confidence: 63%
“…Applications in economics, especially the surveillance of business cycles, are treated for example by Andersson et al (2004) and Andersson et al (2005). Predicting the future state of the economy is important both to governments and to businesses.…”
Section: The Need For Surveillance In New Areasmentioning
confidence: 99%
“…Using parametric assumption regarding Ii based on the previous pattern, there is always the risk that the current cycle is different from the previous ones, which results in a miss-specification of Ii. In (17) it is demonstrated that a miss-specification of the trend after the turn is not so serious. But if both the trend before and after the turn, i.e.…”
Section: Miss-specification Of Outbreak Trendmentioning
confidence: 99%
“…There have some methods to predict the cyclical turning points of economic fluctuation such as function fitting and time series prediction, etc. But these methods emphasize static function dependency or dynamic propagation of time series [2,3] so that the static and dynamic information can not be consistently combined.…”
Section: Introductionmentioning
confidence: 99%